PHOTOGRAPHY IN HISTORICAL EXPLANATION: SOCIAL PRACTICES, DISCURSIVE SPACES AND ARCHIVE - Cornejo, Tomás (Revista de Historia Social y de las Mentalidades, 2025)
This article offers a methodological reflection on the use of photography in the construction of historical knowledge. It underscores the necessity of conducting a thorough documentary critique to evaluate the heuristic potential of photography, much like other types of sources or remnants in historiographical work. Using a photographic portrait preserved in a Chilean archive, the analysis delves into three essential dimensions—social practices, discursive spaces, and archives—that must be considered to effectively integrate this type of document into historical research.